2013
DOI: 10.1136/emermed-2013-202338
|View full text |Cite
|
Sign up to set email alerts
|

A population based study on the night-time effect in trauma care

Abstract: The night-time effect in trauma care was demonstrated for the first time and was maximal in transferred cases. This may explain why it was not found in previous studies where these patients were mostly excluded. Also, the use of population based data-whereby patients not accessing trauma centre care and presumably receiving poorer care were included-may have contributed to the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Therefore, the care of injured patients requiring emergency trauma surgery is extremely time sensitive. Di Bartolomeo et al [ 43 ] recently studied patients transferred with severe injuries and found that patients who were not brought directly to a level I trauma center were more likely to be affected by the off-hour effect. Di Bartolomeo suggested that the off-hour effect in trauma care could be used as a quality indicator [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the care of injured patients requiring emergency trauma surgery is extremely time sensitive. Di Bartolomeo et al [ 43 ] recently studied patients transferred with severe injuries and found that patients who were not brought directly to a level I trauma center were more likely to be affected by the off-hour effect. Di Bartolomeo suggested that the off-hour effect in trauma care could be used as a quality indicator [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that this factor does not have an aggravating effect, 7 , 8 , 9 , 10 while others show that it has a negative influence. 11 , 12 , 13…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Di Bartolomeo et al could demonstrate an off hour effect on trauma patients. This effect was most evident in transferred cases [37]. In other medical emergencies, like stroke [38][39][40][41] or myocardial infarction [42,43] previous studies didn't come to a consistent conclusion regarding the impact of the hospital admission time on the outcome.…”
Section: Discussionmentioning
confidence: 87%